P.077 A Concussion-U educational presentation improves knowledge and attitudes of concussion amongst elite female high-school hockey players. (17th June 2016) - Eagles, M; Powell, M; Bradbury-Squires, D; Murphy, J; Campbell, G; Fletcher, J; Maroun, F
Abstract : Background: Research has suggested that female athletes have a higher incidence of concussion compared to their male counterparts. As such, programs designed to improve knowledge and attitudes of concussion should target this high-risk population. Previous work demonstrated the effect of a novel Concussion-U educational presentation on knowledge and attitudes of concussion amongst male Bantam and Midget AAA hockey players. The objective of this study was to determine if the same presentation was effective in improving the knowledge and attitudes of concussion in a cohort of elite female hockey players.Methods: 26 elite female high-school aged (14-17) hockey players from the province of New Brunswick consented to participate in the study. Each participant completed a modified version of Rosenbaum and Arnett's Concussion Knowledge and Attitudes Survey questionnaire immediately before and after a Concussion-U educational presentation. Results were compared across the two time-points to assess the effectiveness of the presentation.Results: Concussion knowledge and attitude scores significantly ( p <.001) increased from pre-presentation to post-presentation by 12.5% and 13.4%, respectively.Conclusions: A Concussion-U educational presentation resulted in increased knowledge and improved attitudes towards concussion in elite female hockey players. Future research should examine the long-term retention of these improvements.